Synthesis and Biological Activity study of some New Isonicotinic Acid Hydrazide (isoniazid) Derivatives - Salem Abass, Kareem (University of Thi-Qar Journal of Science, 2009)
The work was included the synthesis of some new allyl , vinyl , tosyl and methyl derivatives for isonicotinic acid hydrazide( isoniazid ). The products were characterized by elemental analysis besides the IR and 1H-NMR spectroscopic identifications .The work was also included the study of the biological activity of the products , starting material (isoniazid) and some antibiotics ,. This study shows that the biological activity of products is more than that of the isoniazid and the antibiotics.